The determinants of indulgence in corruption among law enforcement personnel in Malaysia / I.K. Norziaton dan Zatun Najmiah Mohd Sabri - Norziaton, I.K.; Mohd Sabri, Zatun Najmiah (Accounting Research Institute (ARI), 2022)
This study investigated the determinants of indulgence in corruption among law enforcement agency personnel in Malaysia. This study focussed on three law enforcement agencies in Malaysia, the Royal Malaysia Police Department, the Road and Transport Department, and the Immigration Department. The Fraud Diamond Theory was used to form the framework and develop the hypotheses. It concerns corruption among law enforcement personnel using the four elements: capability, pressure, rationalization, and opportunity. There were four hypotheses developed in this study. The researcher used face-to-face and online surveys (questionnaires) as data collection method and the participation of respondents was voluntary. 150 questionnaires were issued for the collection of data through an online survey and face-to-face interviews. The data collection process took two months, from May 2020 to June 2020. In the earlier part of the data collection process, 63 questionnaires were obtained, while 79 questionnaires were received towards the end of the period. Based on the findings, there is a significant positive correlation between self-influence and family influence-related and the indulgence in corruption among law enforcement personnel. This research indicated that family pressure and self-influence attributes were accepted. However, another two attributes namely public perception and peer pressure, were rejected. This study has important implications for national or international policymakers to acknowledge that anti-corruption policies play a crucial role to curb corruption among law enforcement agencies and understand the need to adopt these anti-corruption policies according to each nation’s economic and cultural context.